Experimental investigation of the response of buried pipelines to surficial loads - Rogenbuke, Peter. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Buried pipes serve as the lifelines of modern cities and therefore have the utmost importance for today’s society. Owing to their buried state, it is not easy to detect damages; therefore, extra caution in their design is required to prevent irreparable damages. As deformation is generally caused by excessive stresses, one way to reduce the imposed stresses acting on the pipe is to use geosynthetic materials, since these materials reduce stresses on the pipe by distributing stresses more uniformly,at the same time increasing the bearing capacity of the soil. The critical parameters controlling the magnitude of stresses acting on the pipe are the burial depth, soil’s relative density, placement depth of geosynthetic layers, the number of geosynthetic layers and material properties of the pipe. For this purpose in this study, small- scale laboratory experiments were conducted ın a rigid box at 1g to observe the effects of these parametes on pipe stresses and the bearing capacity of the soil with and without a buried pipe. Strain gauges were used to record the pipe stresses, and backfill material of choice was sand. In the model experiments, a model footing was loaded until a pre-selected settlement threshold is reached. LVDT transducers and load cells were used to measure the settlement and load values, respectively. Resulting displacements are determined by analyzing consecutive photographs of the evolving tests using MATLAB based Particle Image Velocimetry (PIV) software. A total of 26 experiments were conducted, nine without geogrid reinforcements and the rest with geogrid reinforcements, at different relative densities. Obtained results are discussed in this work.
Keywords: Underground pipelines.; Road loads.